Politics, Ethics and Strangers in the 21st Century Fifteen critical reflections on Jacques Derrida’s concept of hos(ti)pitality - Makris, Spiros (Theoria and Praxis: International Journal of Interdisciplinary Thought, 2017)
In contrast to the Kantian concept of conditional hospitality, which is a political and a diplomatic term, Jacques Derrida’s concept of hos(ti)pitality is without a doubt a pure ethical and messianic experience of an encounter between strangers who at any moment could be perceived as each other’s enemy. Since the 1990s, the French philosopher via this neologism put the human condition and especially the modern state sovereignty under question. From this point of view, hos(ti)pitality is conceived in this article as a phenomenological event; a miracle without religion; something that sharply interrupts the natural order of things by rearranging the world and its meanings in such a radical way that the householder becomes the guest and the stranger becomes the host. Hamletian-inspired hos(ti)pitality is first and foremost a Derridean hauntology of absolute Other which means a work of justice in a world full of pariahs. Derridean theory of hos(ti)pitality is without a doubt the proper way to explore in-depth the challenges of pure hospitality as an opportunity to make the messianic impossible become a historical truth. So, our main thesis here is that insofar as the conventional meanings of such keywords as refugee, exile, deportee, displaced person and foreigner have changed rapidly within the textual and contextual manner of the work of Derridean deconstruction as a work of mourning, the so-called Benjaminian and Arendtian pariahs in the 21st century take an important position in discourse analysis as a whole.